2012
DOI: 10.1002/clc.21977
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine‐Using Patients With a Normal or Nondiagnostic Electrocardiogram: Single‐Photon Emission Computed Tomography Myocardial Perfusion Imaging and Outcome

Abstract: Background Few trials have examined the outcomes of patients who use cocaine with chest pain and who have a normal or nondiagnostic electrocardiogram (ECG) and the use of single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI). Hypothesis We sought to compare the characteristics and overall outcomes in cocaine users vs non-cocaine users presenting to the emergency department with a normal/nondiagnostic ECG and to assess the value of rest MPI in both of these populations. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In such patients, SPECT MPI was able to reliably predict myocardial infarction and/or need for percutaneous intervention and reduce unnecessary admissions [75]. Cost-effectiveness analyses suggest that for patients at intermediate risk of coronary artery disease, SPECT MPI provides a more costeffective approach, due largely to greater accuracy, than a stress ECG [76].…”
Section: Diagnosismentioning
confidence: 96%
See 2 more Smart Citations
“…In such patients, SPECT MPI was able to reliably predict myocardial infarction and/or need for percutaneous intervention and reduce unnecessary admissions [75]. Cost-effectiveness analyses suggest that for patients at intermediate risk of coronary artery disease, SPECT MPI provides a more costeffective approach, due largely to greater accuracy, than a stress ECG [76].…”
Section: Diagnosismentioning
confidence: 96%
“…In the recent Emergency Room Assessment of Sestamibi for Evaluation of Chest Pain (ERASE Chest Pain) trial, Hendel et al [75] identified single-photon emission computed tomography myocardial perfusion imaging (SPECT MPI) as a useful diagnostic tool in cocaine-using patients with symptoms of myocardial ischemia and a normal or non-diagnostic ECG. In such patients, SPECT MPI was able to reliably predict myocardial infarction and/or need for percutaneous intervention and reduce unnecessary admissions [75].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Ruling out cardiac events more rapidly should involve the use of additional imaging, provocative testing, or more frequent serum biomarkers for detecting myocardial damage. Hendel and colleagues reported on the use of single-photon emission computed tomography myocardial perfusion imaging (MPI) in 151 patients with cocaine chest pain and found that it effectively ruled out cardiac events and lowered admission rates 15. Paraschin and colleagues applied cardiac CT angiography (CTA) in 24 cocaine users presenting with chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Hendel and colleagues reported on the use of single-photon emission computed tomography myocardial perfusion imaging (MPI) in 151 patients with cocaine chest pain and found that it effectively ruled out cardiac events and lowered admission rates. 15 Paraschin and colleagues applied cardiac CT angiography (CTA) in 24 cocaine users presenting with chest pain. They found that cardiac CTA was normal in 96% of patients, and positive in only 1 patient (4%) who had non-significant coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%